Planejamento tributário sob a óptica do estado: um estudo sobre a eficiência da arrecadação tributária brasileira e a delegação onerosa da capacidade ativa tributária de cobrança de certidão de dívida ativa - Faganello, Rafael Albertoni (2018)
The objective of this research is to provide better tax efficiency subsidies based on measures that can be adopted, preferably, by the three federal levels of Brazil, as well as to demonstrate that the adjustment of the tax collection mechanism will bring greater efficiency in the collection itself, bringing, too, a reduction of public expenditures for such an inspection, confident of a moralistic change in taxpayer behavior in relation to tax evasion. The idea of the work was, therefore, to find a method to increase the collection without increasing or creating tribute, besides finding legal validity for this mechanism. In addition, increasing efficient collection, without increasing taxes, implies a greater provision of government budget to promote public policies. The method was to contextualize the taxpayer’s tax planning arguments to be compatible with the tax planning of the government in order to justify the duty to increase the collection of taxes through onerous delegation for the collection of already consolidated tax credits, but which are not advantageous if objects of tax execution or long tax installments without guarantees